Problem bezpieczeństwa w mieście - Jasina, Karolina; Szubart-Jaszczur, Kinga (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
Social security has become in recent years an important element in the discourse about the quality of life on individualism and social group. It’s one of the basic needs which is crucial for every human being in everyday life. This article consists of two parts: short theoretical admission and the main, empirical part. Safety determines; threats and risk. Rating sense of the safety of residents in city should be considered through the prism of the items listed above. This article present a problem of safety and the fear of crime in modern society, especially in cities on the example of Rzeszow. The aim of the research has been to present respondent’s preferences for sense of security. In research areas, respondents assessed the dangers in Rzeszow. The survey also confirmed a lack of correlation between the sense of security and the real level of recorded crime.
Keywords: needs; social security; crime; dangers; risk